Contralateral knee osteoarthritis severity relates to magnetic resonance imaging findings in knees with and without osteoarthritis: Data from the osteoarthritis initiative - Jeffrey B. Driban; Jonggyu Baek; Julieann C. Patarini; Emily Kirillov; Nhung Vo; Michael J. Richard; Ming Zhang; Matthew S. Harkey; Grace H. Lo; Shao-Hsien Liu; Charles B. Eaton; Jamie MacKay; et al. (Osteoarthritis and Cartilage Open)
Objective: We explored whether a magnetic resonance imaging (MRI)-based composite score of bone marrow lesion and effusion-synovitis volumes related to contralateral knee osteoarthritis disease severity. Design: Using data from the Osteoarthritis Initiative, we conducted cross-sectional knee-based analyses among participants with bilateral knee MRIs and at least one knee with Kellgren–Lawrence (KL) grade ≥1 and a WOMAC pain score ≥10/100 (n ​= ​693). Bone marrow lesion and effusion-synovitis volumes on MRIs were used to calculate a composite score (“disease activity”). We divided the disease activity score into tertiles. We used multinomial logistic models to explore the association between disease activity in knees with and without radiographic osteoarthritis (outcome) and the contralateral disease severity (KL grade or disease activity; exposure). Results: We included 1386 knees from participants with an average age of 62 (standard deviation ​= ​9) years. Most participants were overweight and had mild-to-moderate radiographic osteoarthritis. Disease activity among knees without radiographic osteoarthritis had statistically significant relationships with contralateral disease activity (range of odds ratios: 4.86–23.22) but not contralateral KL grade (range of odds ratios: 0.86–1.01). Disease activity among knees with radiographic osteoarthritis had statistically significant relationships with contralateral disease activity and KL grade; however, the association was stronger for contralateral disease activity than KL grade (range of odds ratios: 3.67–21.29 versus 1.96–2.20). Conclusion: Structural findings in one knee may relate to structural findings in the other knee. This highlights the need for future studies to explore how the contralateral knee could impact clinical trial screening, monitoring, and intervention strategies, especially when testing localized therapies.